The effect of negative childhood experiences and gambling cognitive constructions on gambling behavior and its causes in young adulthood period - AVCU, AKİF (My University, 2022)
This study aimed to examine the cognitive structures and negative childhood experiences of young adults about gambling on gambling behavior and its causes. The study group consisted of 232 young adults aged 18–30 years from Gaziantep, Elâzığ, Malatya, Antalya, and İstanbul provinces who exhibited gambling behavior. Participants were provided a personal information form and examined using the South Oaks Gambling Screening Test, the Cognition Scale for Gambling, the Reasons for Gambling Scale, and the Childhood Negative Experiences Scale. The results revealed that the cognitive structures related to gambling affect gambling behaviors (= .714; p < .01) positively. Cognitive structures explained 13% of the change in the reasons for gambling and childhood negative experiences and cognitive structures explained 52% of the change in the reasons for gambling. It was also found that sociodemographic variables have an effect on gambling behavior and its causes. Finally, cognitive structures related to gambling and negative childhood experiences indirectly risk gambling behavior.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Social Sciences and Humanities; Psychology; Clinical Psychology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); PSİKOLOJİ, KLİNİK; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; PSYCHOLOGY, CLINICAL; General Psychology; Psychology (miscellaneous); Social Sciences & Humanities